The politics of e-gov: the upcoming struggle for redefining civic engagement. - Toregas, Costis (National Civic Review)
Part of a special issue on digital democracy. The writer discusses the democracy aspects of e-government (e-gov). He contends that the comparative ease with which e-gov allows a citizen to contact a government official will lead to profuse expression of opinion and concern. In addition, he asserts that the current government system is not equipped to manage the potential for conflict generated by this situation or find ways to absorb the potential enthusiasm of an online citizenry. Furthermore, he argues that conflict could dampen the positive forces that the new e-gov potential offers civic engagement landscape. To examine the issue he looks at its inputs, the process acting on and transforming the inputs, and the outputs that are produced.